Microlaimus capitatus sp. n. and Dichromadora simplex Timm, 1961 (Nematoda, Chromadorea) from the coast of Vietnam - Gagarin, Vladimir G. (Zootaxa, 2020)
Two nematode species isolated from sediments of the littoral zone of the South China Sea on the coast of Vietnam are described and illustrated. Microlaimus capitatus sp. n. is closely related to M. affinis Gerlach, 1958 and M. amphidius Kamran et al., 2009, but differs by having a thin, poorly developed pharyngostom, more posterior vulva and presence of terminal setae on the tail. The female of Dichromadora simplex Timm, 1961 is described and illustrated for the first time.